Electromyography and range-of-motion measurements in German soldiers wearing different types of body armour while marching - Lang, Patricia; Amann, M.; Riesner, H. J.; Friemert, B.; Siebers, H.; Betsch, Marcel; Palm, H. G. (BMJ Military Health, 2024)
Introduction In this study, we used surface electromyography (EMG) electrodes in order to measure and compare activity in the neck, back and thigh muscles of soldiers wearing two different types of body armour. A secondary objective was to analyse shoulder and hip ranges of motion using inertial motion sensors. Methods Fourteen male soldiers were instructed to march 6 km on a treadmill while wearing different types of body armour. All participants wore shorts and a T-shirt and the same size vest regardless of their body size. We measured back and thigh muscle activity as well as shoulder and hip ranges of motion at regular intervals during the march. Results Over the course of a 6 km march, muscle activity was already increased to 1.3 to 2.0 times after putting on the vest and increased by up to 13 times during the march with equipment. The new vest with hip belt required higher levels of muscle activity. Conclusions Body armour with hip belt placed higher levels of stress on back and neck muscles during a 6 km march than without. There was no major difference between the two types of body armour in terms of thigh muscle activity.
CRIS-Team Scopus Importer:2024-07-12